Help-seeking behaviors and the mental well-being status of Albanian immigrants in Malaysia - Thartori, Voltisa (Kulliyyah of Education, International Islamic University Malaysia, 2021)
Immigration causes significant challenges for immigrants. Numerous factors contribute to psychological stress in immigrant populations moving to a new country. The feeling of loss, language barriers, lack of financial support, employment difficulties, discrimination, limited social support, and many other stressors affect the emotional wellbeing of immigrants. The purpose of this qualitative study was to explore and investigate the life experiences of 16 Albanian and Kosovo-Albanian immigrants living in Malaysia, as well as those who previously lived in Malaysia and currently live overseas in Australia and Albania. Specifically, the study explored the following: (i) Immigrants' psychological health and issues in order to determine their perception and attitude towards mental wellbeing; (ii) The obstacles and barriers immigrants face in Malaysia; (iii) The immigrants' coping strategies for their mental wellbeing; (iv) The role of stigmatisation in the help-seeking behaviour of immigrants; and (v) Suggestion and recommendation to live in Malaysia. Qualitative phenomenological case study using in-depth semi-structured interviews was the vehicle through which the data was collected. The result showed that indicators of mental wellbeing such as inner peace, mental, psychical and spiritual health, happiness, gratefulness, purpose in life, accomplishment, fulfilling family needs, balanced life, and self and life improvement positively affected the immigrants' mental wellbeing. However, cultural shock, visa and employment pass issues, difficulty to obtain PR status, difficulty to secure employment status, foreigner and orang putih, and lack of family support negatively affected the wellbeing of the immigrants. Furthermore, Albanian immigrants felt safer to share their burden and challenges with family and close friends because they wish to keep their problems a secret and to avoid outsiders' perception. This fear of people's perception is closely associated with stigma. Hence, they felt that there is a need to hide anything which they deem wrong, to avoid a bad name, and to maintain the right image within the Albanian community. To deal with psychological problems, they resort to several strategies which include calmness, prayer, patience, and having a positive attitude in solving and analysing problems. According to the respondents, Malaysia is a country which offers many opportunities in terms of education and business. Finally, the participants voiced their suggestions to policymakers, social workers, psychologists and academicians to improve the state of wellbeing of Albanian diaspora immigrants as well as other immigrants residing in Malaysia.